Hydrogen embrittlement in an AISI 1045 steel component of the sugarcane industry - Marcelo, A. L.; Tokimatsu, R. C. [UNESP]; Ferreira, I. (Pergamon-Elsevier B.V. Ltd, 2009)
This paper will present a failure analysis of a chain component, manufactured with AISI 1045 steel and used for sugarcane transport. During the fabrication process, this component is submitted to induction hardening, just on one surface, before the galvanizing process. The occurrence of surface cracks, during storage, disables the usage of these components. Chemical and metallographic analyses, tensile, fracture toughness, and hardness tests, and fractography were conducted in order to determine the causes of failure. The steel chemical composition was in accordance with AISI 1045. The metallographic analyses and fractography did not exhibit the presence of zinc into the cracks; this is an indication that the cracks occurred after the galvanizing process. Tensile and fracture toughness test results are as expected. The crack surface and the fracture toughness specimen surfaces showed two different fracture micromechanisms: dimples and intergranular. The delayed fracture associated with the predominance of intergranular fracture micromechanism at the induction hardened layer and the high hardness level is a clear indication of the hydrogen embrittlement. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Failure analysis; Hydrogen embrittlement; Intergranular fracture micromechanism